2014
DOI: 10.1007/s00436-014-3911-z
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a new gelled nested PCR test for the diagnosis of imported malaria: comparison with microscopy, rapid diagnostic test, and real-time PCR

Abstract: Microscopy and rapid diagnostic tests (RDTs) are the techniques commonly used for malaria diagnosis but they are usually insensitive at very low levels of parasitemia. Nested PCR is commonly used as a reference technique in the diagnosis of malaria due to its high sensitivity and specificity. However, it is a cumbersome assay only available in reference centers. We evaluated a new nested PCR-based assay, BIOMALAR kit (Biotools B&M Labs, Madrid, Spain) which employs ready-to-use gelled reagents and allows the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In this respect, microscopic diagnosis alone (TkS or QBC with TnS) remains a frequently used strategy in France for malaria diagnosis [6]. However, as observed in our study, its sensitivity is thought to be no higher than 90% in nonendemic countries when compared to PCR [14,23], and it depends on infecting species, geographic origin and the microscopist's experience [23], which can be limited in nonendemic regions. A study by the French National Reference Centre for Malaria showed that 43.7% of 986 city and hospital medical laboratories did not have any cases of malaria in a year [21].…”
Section: Discussionmentioning
confidence: 70%
“…In this respect, microscopic diagnosis alone (TkS or QBC with TnS) remains a frequently used strategy in France for malaria diagnosis [6]. However, as observed in our study, its sensitivity is thought to be no higher than 90% in nonendemic countries when compared to PCR [14,23], and it depends on infecting species, geographic origin and the microscopist's experience [23], which can be limited in nonendemic regions. A study by the French National Reference Centre for Malaria showed that 43.7% of 986 city and hospital medical laboratories did not have any cases of malaria in a year [21].…”
Section: Discussionmentioning
confidence: 70%
“…This method has been in use for century and has been the main tool for diagnosis of malaria in laboratories [7]. This method is relatively simple and requires less training of the microscopists; with an average sensitivity of about 50-100 parasites per microliter of blood [8,9]. Also, this method detects different species of Plasmodium in specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, this method is increasingly in use for diagnosis of malaria parasite due to the fact that it is rapid, easy to use and does not require much training or special equipment [10]. However, there are limitations to the use of this method because the method is not sensitive to identify different species of Plasmodium and the low sensitivity to detect parasitemia, if the intensity is less than 100 parasites per microliter of blood [11,9]. Molecular technique of detecting malaria parasite is a very sensitive and accurate method of malaria diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…These methods have a specific use, as they are limited to the measurement of past exposure to the disease. Methods based on parasite nucleic acid detection [ 11 ] have shown great sensitivity and specificity, but require significant infrastructure and training, and are more expensive than the blood smear method [ 12 ]. Methods based on the use of antibodies to recognise parasite components or biomarkers have also emerged in recent years [ 13 ].…”
Section: Introductionmentioning
confidence: 99%